Developing an Integrated Solid Waste Management System for a Mini – Municipality in Tobruk – Libya - Aisha F Jarbou; Aisha E Abdunnabi (Libyan Journal of Medical and Applied Sciences, 2025)
In an attempt to solve problem of solid waste management in Tobruk, Libya, a field study of the services provided for solid waste management in 2012. Showed that these services were below the poverty level. The main objective of the study was to propose a comprehensive and sustainable solid waste management system. It was necessary to define the elements and criteria quantitively for the comprehensive design of solid waste which were as follows: a) The population 0f the city of Tobruk has reached 110,300 capita distributed over 20 neighborhoods, b) The total amount of waste to 120 ton per day c) The daily average of household waste generation reached 1.02 ± 0.29 Kg as household solid waste with a total of 111.78 ton per day; e) the estimated average household solid waste per neighborhood was 5.59±2.58 ton city is mainly urban with good roads network made of a good number of rate was 1.02 ± 0.29 Kg as household solid waste with a total of 111.78 ton per day. e) the estimated average household solid waste per neighborhood was 5.59±2.58 ton /day. a population density of 562.7. it was possible to design a sustainable comprehensive and integrated system. The proposed system consisted of the following: workforce of 831 workers and139 drivers and 38 supervisors, a managerial staff of 73, a total number of various type and capacity of containers 809, a transportation fleet of various trucks and vehicles of 55.